Application Of Hilti Onestep Bolts For Roadway Support In German Deep Coal Mines - Michael Bayerl (International Conference on Ground Control in Mining, 2009)
The HILTI OneStep rockbolt was implemented for roadway development in German deep coal mines in 2004. The development by HILTI Company is based on a technical joint venture with RAG Deutsche Steinkohle AG. The technical development of a One-Step bolting system was required for weak strata conditions at the roadway development face. Standard resin bolting has reached the limit of performance when boreholes are squeezed and cannot be filled with capsules. In some cases the heading face is brittle and requires additional support for installation of the bolts and a person working immediately next to the borehole. The Hilti One-Step system allows automated and safe processing at the heading front and provides the key technique to avoid these problems.